2019
DOI: 10.1038/s41598-019-47244-y
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease virus mediated apoptosis and migration inhibition of human oral cancer cells: A probable role of β-catenin and matrix metalloproteinase-7

Abstract: Cancer cell metastasis and its dissemination are most enigmatic and challenging aspects in the development of its therapeutics. Newcastle disease virus (NDV) is a well-studied avian paramyxovirus frequently isolated from birds and rarely from mammals. Since the first report of its oncolytic property, many NDV strains were studied for its effect in various cancer cells. In the present study, NDV strain Bareilly was characterized for its apoptotic potential and migration inhibition in human oral cancer cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Our further analysis revealed that E-exos can activate Wnt/β-catenin signaling and upregulate the expression of MMP-7. MMP-7 is a crucial member of the matrix metalloproteinase (MMP) family, and it is involved in cell invasion of various cancers. , In the process of re-epithelialization of the wound, MMPs promote the breakdown of collagen or other structural compounds and, therefore, play an indispensable role in the movement of keratinocytes . MMP deletion damages the migration of cells and results in wound-healing defects .…”
Section: Discussionmentioning
confidence: 99%
“…Our further analysis revealed that E-exos can activate Wnt/β-catenin signaling and upregulate the expression of MMP-7. MMP-7 is a crucial member of the matrix metalloproteinase (MMP) family, and it is involved in cell invasion of various cancers. , In the process of re-epithelialization of the wound, MMPs promote the breakdown of collagen or other structural compounds and, therefore, play an indispensable role in the movement of keratinocytes . MMP deletion damages the migration of cells and results in wound-healing defects .…”
Section: Discussionmentioning
confidence: 99%
“…Cells were incubated with virus for 2 hours, followed by washing with DMEM media to remove unattached virus. Cells were then incubated at 37°C and 5% CO 2 for 3 days ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, TRAIL-armed oncolytic poxvirus inhibits lung cancer cells by inducing apoptosis ( Hu et al., 2018 ). NDV decreased mitochondrial membrane potential, suggesting an intrinsic pathway of apoptosis in oral cancer cells ( Morla et al., 2019 ).…”
Section: Oncolytic Virus-regulated Induction Of Apoptosis Of Tumor Cellsmentioning
confidence: 99%